Collaborative Information Behaviour of Engineering Students - Saleh, Nasser; Large, Andrew (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Collaborative information behaviour is an emerging area in information science that studies when two or more actors identify, seek, search, and use information to accomplish a task. This paper reports on a recent research investigating the collaborative information behaviour of undergraduate engineering students in the context of engineering design group projects. Le comportement informationnel collaboratif est un sujet émergent en sciences de l’information qui s’intéresse aux moments où deux acteurs ou plus cherchent, repèrent, sélectionnent et utilisent l’information pour accomplir une tâche. Cette communication présente une étude récente sur le comportement informationnel informatif des étudiants en génie dans le contexte de projets de groupe en conception technique.